(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2009)
The author deals with the place of witness and testimonies in the Guzmán’s documentary La memoria obstinada. It places the Guzman’s film in the early transition context, where survivors had not the public centrality that they have today. The author analizes how the film tries to bring to the present an experience of repression wich has been set in the past.